Geographic Information System (GIS) Spatial Analysis to Detect the Distribution Pattern of Unused Land Fires at Ogan Ilir Regency - Sunarto; Sobri, Kiagus Muhammad; Alfitri; Nadjib, Abdul (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2024)
Land fires pose a serious threat to the environment and communities in Ogan Ilir Regency, South Sumatra. This study aims to analyze the distribution pattern of land fires using GIS spatial analysis technology. Through Sentinel-2 image classification and fire intensity analysis, it had been identified focal points of dormant land fires mainly in South Indralaya, North Indralaya, and West Pemulutan sub-districts. The results of this study provide in-depth insight into the spatial distribution of land fires and the factors that influence their occurrence. This research also produced a map of the distribution of fire hotspots in unused land areas.  From the research, it can be concluded that spatial analysis can map in detail and comprehensively the burning locations on unused land. The implication of this research is the need to develop more effective mitigation strategies to address the risk of land fires in the future. Therefore, this study not only makes an important contribution to the scientific literature but also offers new directions for research and policy focused on sustainable and effective land fire risk management.